The Relationship Between Nurses\' Trust In And Identification With Hospital Goals And Their Effort To Improve Continuously In Private Hospitals Of Shiraz - Mohammad Ali Nadi; Mohammad Hossein Yarmohammadian (Tehran University of Medical Sciences, 2013)
Background and Aim: Based on theories and researches, two variables effective in the continuous improvement of services are trust in and identification with hospital goals. The present study aims to explore the relationship between such variables among nursing staff members in private hospitals of Shiraz. Materials and Methods: This research is a cross-sectional correlation study. Some 340 nurses(58 males and 282 females) were selected using the stratified sampling technique. Three questionnaires for the assessment of identification with hospital goals, measurement of continuous improvement, and determination of trust in hospital were used. The reliability of data collection devices turned out to be 0.70, 0.70 and 0.79, respectively. Besides, the construct validity was confirmed through factor analysis. Data were analyzed inferentially using Pearson's correlation test and hierarchical regression analysis. Results: The findings show that the relationship between identification with hospital goals and trust and nurses' effort to improve continuously is positive and significant. Moreover, the results of hierarchical regression analysis show that after controlling gender, age, experience and education, first identification with hospital goals and then trust in hospital play a significant role in the effort to improve continuously. Conclusion: Nurses' effort to improve continuously is mostly influenced by identification with hospital goals rather than trust in hospital.